Impact of financial leverage on profitability of listed manufacturing firms in China - Dalci, Ilhan (Emerald Group Publishing Ltd, 2018)
Purpose The purpose of the study is to explore how financial leverage influences profitability of 1,503 listed manufacturing firms in China. Design/methodology/approach The sample of the study is composed of the listed manufacturing firms in China. For the manufacturing firms, the annual financial information from 2008 to 2016 is obtained from the ORBIS database. In this study, initially a simultaneous equation approach is used to control for potential endogeneity. Then, additional regression analyses are conducted with panel data over the period of 2008-2016 using OLS, Fixed-effects, First-difference, Random-effects and Arellano and Bond's (1991) two-step Generalized Method of Moments (GMM) methods. Findings The results reveal that the impact of leverage on profitability is inverted U-shaped. In this inverted U-shaped relationship, the positive impact of financial leverage on profitability could be attributed to tax shield, whereas the negative impact might be because of bankruptcy cost, financial distress, severe agency problems and information asymmetry that the listed Chinese firms suffer from because of some institutional characteristics of China. Research limitations/implications First, this study focuses on only listed manufacturing firms in China. Second, ownership types are not taken into account in this study. Practical implications First, the Chinese government should direct its efforts toward developing the bond markets and promoting alternative privately owned loan creditors to state-owned banks. Parallel to this, the transformation process toward market economy should be accelerated to facilitate the privatization of state-owned enterprises (SOEs). In addition to this, development of the bond market and privatization of SOEs will also mitigate the agency conflict between creditors and managers and between shareholders and managers. Originality/value To the best of the author's knowledge, this is the first study which investigates the impact of capital structure on profitability of the listed firms in China.
Keywords: China; Profitability; Leverage; Capital structure